Risk management: a new dimension in health management - Ahmad Farid AR,; Haidar Rizal T,; Jamsiah M,; Khalib AL, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2009)
Introduction : Health management is a tool to ensure an effective running of health program and at the same time avoiding flaws to its components including patients, workers and the entire organization. Risk management is a new concept in health management where the determinants of the problems or the risks are put to minima. It’s strategies are oriented towards prevention as well as controlling to all its administrative system. Methodology : This is a systematic review on various papers, studies and observations put forwards by risk management experts. It is also supported by feedbacks from many scholars who are involved in research and teaching. Results : It is been observed that risk management activities have been on practiced in health care delivery system. It is not a new form, but rather a situational action based on certain issues. In fact, it happens in any organization – public or private. Close observation on this area has triggered development of various risk management models including some administrative standard and guidelines. Conclusion: Risk management is a new approach that need to be practiced by all manager and leader. Its discipline involves interpretation of risk at all angles. It is not only confined to the explicit component, but should also be expended to others area as well. It needs a good sense and good attitude of the manager. The essence of risk management is to minimize the risk to patient, staff, public and the entire organization.